Association of Epicardial Adipose Tissue Adipocytes Hypertrophy with Biomarkers of Low-Grade Inflammation and Extracellular Matrix Remodeling in Patients with Coronary Artery Disease - Irina V. Kologrivova; Natalia V. Naryzhnaya; Olga A. Koshelskaya; Tatiana E. Suslova; Elena S. Kravchenko; Olga A. Kharitonova; Vladimir V. Evtushenko; Alla A. Boshchenko (Biomedicines, 2023)
The aim of the study was to compare the morphological features of epicardial adipose tissue (EAT) adipocyte with the circulating inflammatory biomarkers and parameters of extracellular matrix remodeling in patients with coronary artery disease (CAD). We recruited 42 patients with CAD (m/f 28/14) who were scheduled for coronary artery bypass graft surgery (CABG). EAT adipocytes were obtained by the enzymatic method from intraoperative adipose tissue samples. Concentrations of secreted and lipoprotein-associated phospholipase A2 (sPLA2 and LpPLA2), TNF-α, IL-1β, IL-6, IL-10, high-sensitive C-reactive protein (hsCRP), metalloproteinase-9 (MMP-9), MMP-2, C-terminal cross-linking telopeptide of type I collagen (CTX-I), and tissue inhibitor of metalloproteinase 1 (TIMP-1) were measured in blood serum. Patients were divided into two groups: group 1—with mean EAT adipocytes’ size ≤ 87.32 μm; group 2—with mean EAT adipocytes’ size > 87.32 μm. Patients of group 2 had higher concentrations of triglycerides, hsCRP, TNF-α, and sPLA2 and a lower concentration of CTX-I. A multiple logistic regression model was created (RN2 = 0.43, p = 0.0013). Concentrations of TNF-α, sPLA2 and CTX-I appeared to be independent determinants of the EAT adipocyte hypertrophy. ROC analysis revealed the 78% accuracy, 71% sensitivity, and 85% specificity of the model, AUC = 0.82. According to our results, chronic low-grade inflammation and extracellular matrix remodeling are closely associated with the development of hypertrophy of EAT adipocytes, with serum concentrations of TNF-α, sPLA2 and CTX-I being the key predictors, describing the variability of epicardial adipocytes’ size.